Development of scientific concepts on abuse of law in national jurisprudence - K. M. Hurtova (Bulletin of Kharkiv National University of Internal Affairs)
The article defines the abuse of law as one of the most important problems of modern legal science, as well as a complex and controversial legal category, the relevance of which is directly related to the level of development of democracy, stability in the state and society, traditions of law-abiding and strict observance of human and citizen rights, research which have both theoretical and applied interest for the development of domestic legal science.